Efektivitas Pendistribusian Zakat, Infaq, dan Shadaqah pada Masa Pandemi COVID-19 di BAZNAS Kabupaten Ngawi - Kahfi, Rayyan Ashhabul; Futaqi, Faruq Ahmad (Institut Agama Islam Negeri Ponorogo, 2022)
This study aims to find out how the mechanism for distributing zakat infaq and shadaqah and the obstacles during the Covid-19 pandemic in Baznas Ngawi district. The type of research used by the researcher is field research using a qualitative approach. The data used are primary and secondary data by collecting observation data, interviews, and documentation. The results of this study are in the distribution of BAZNAS Ngawi Regency more towards consumptive Constraints faced by the Ngawi Regency BAZNAS institution, namely there are many overlapping points in the distribution of assistance to the community. The effectiveness of BAZNAS in Ngawi Regency is quite good or effective, although there are still shortcomings from BAZNAS because the time for giving Zakat, Infaq and Shadaqah funds does not go directly to the community but is only entrusted to the management who asks for help. Penelitian ini bertujuan untuk mengetahui bagaimana mekanisme pendistribusian zakat infaq dan shadaqah dan kendala di masa pandemi Covid-19 di Baznas kabupaten Ngawi. Jenis penelitian yang digunakan oleh peneliti adalah penelitian lapangan (field research) dengan menggunakan pendekatan kualitatif. Data yang digunakan yaitu data primer dan sekuknder dengan cara mengumpulkan data observasi, wawancara, dan dokumentasi. Hasil penelitian ini adalah dalam pendistribusian BAZNAS Kabupaten Ngawi lebih kearah konsumtif Kendala yang di hadapi oleh lembaga BAZNAS Kabupaten Ngawi yaitu banyak terjadi tumpang titik dalam penyaluran bantuan ke masyarakat. Efektivitas BAZNAS Kabupaten Ngawi sudah cukup baik atau efektif walaupun masih ada kekurangan dari pihak BAZNAS karena waktu pemberian bantuan dana Zakat, Infaq dan Shadaqah tidak terjun secara langsung ke masyarakat melainkan hanya dititipkan kepada pengurus yang meminta bantuan.